KUALITAS PAPAN KOMPOSIT YANG TERBUAT DARI LIMBAH KAYU SENGON DAN KARTON DAUR ULANG - . Suhasman; Muh. Yusram Massijaya; Yusuf Sudo Hadi (Forestry Faculty of Universitas Hasanuddin, 2006)
The use of recycled carton as an alternative material for the layer of composite board may increase the board strength properties. The objective of this research was to find out the influence of face and back layer types on the quality of produced boards. Materials used in this study were wafer made from sengon wood (Paraserianthes falcataria L. Nielsen), water based polymer isocyanate adhesive, and several kinds of cartons such as duplex carton, recycled carton, and waste of corrugated board. The composite board was produced with the target density of 0.65 g/cm3 and the resin solid content of 6% based on oven dry weight of particle, face and back layers. The results are as follows : 1) Utilization of carton layers improved the dimensional stability and bending strength of board; 2) Composite board with recycled carton layer fullfilled the Japanese Industrial Standard (JIS) A-5908-1994 for wafer board type in terms of density, water content, and modulus of rupture (MOR) in lengthwise and widhtwise of board but, did not fullfill that for veneered particled board type; 3) The presence of those layer material types decreased internal bond of the board. Keywords : composite board, face and back layer types, recyled carton